Perancangan Aplikasi SOL-MATH Untuk Pendidikan Matematika SMP/Sederajat dengan Metode Design Thinking - Arsyillah Majid; Ihza Ghani Sonya; Rizky Rizky (Jurnal Pendidikan Multimedia (Edsence), 2022)
The Covid-19 pandemic has caused a decrease in community mobility, both in the economic sector and in the education sector. Design thinking applications are learning in Indonesia that requires new online and offline-based innovations to continue education during the Covid-19 pandemic since 2020. This aims to answer student complaints who often lose their network or have difficulty understanding the lessons taught by teachers. To make it easier for students to live without face-to-face learning, an education-based application was created with the concept of Offline and Online Learning. An application requires Design Thinking to create an interface that makes it easy for users to run the application. Design Thinking must be made attractive, easy to use, and appropriate for its users.